Understanding depressive symptoms in nursing home residents: the role of frequency and enjoyability of different expanded everyday activities relevant to the nursing home setting - Diegelmann, Mona; Wahl, Hans-Werner; Schilling, Oliver; Jansen, Carl-Philipp; Schnabel, Eva-Luisa; Hauer, Klaus (European journal of ageing, 2018)
Depressive symptoms are highly prevalent in nursing home (NH) residents. We assume that enjoyability, besides frequency of activities, is an important facet of expanded everyday activities (EEAs; Baltes et al., in: Baltes and Mayer (eds) The Berlin aging study, University of California Press, Berkeley, 2001) and affects residents’ depressive symptoms. Furthermore, we assume that associations with depressive symptoms vary for different EEAs, namely contact with co-residents and staff and participation in organized in-home activities. To investigate these associations, longitudinal data from 160 residents (Mage = 83.1 years, SD = 9.8 years, 73% female) of two German NHs, assessed across four measurement occasions each 3 months apart, were analyzed. Depressive symptoms were assessed by the Geriatric Depression Scale-Residential (GDS-12R); the frequency of EEAs and their enjoyabilities were assessed via proxy ratings and interviews, respectively. As data from the completed Long-Term Care in Motion intervention study were used, 49% of the sample also received a physical activity intervention. Generalized linear mixed models were run to test the hypothesized effects as flexibly as possible, accounting for non-normality of the GDS-12R and controlling for residents’ intervention status. The results showed that the interaction effect of the enjoyability of contact with co-residents and contact frequency was relevant for residents’ depressive symptoms rather than the effect of contact frequency alone. The frequency of staff contact was only marginally associated with fewer depressive symptoms. Further, enjoying participating in organized in-home activities was associated with fewer depressive symptoms. In conclusion, findings support our conceptually driven expectation of differential effects in terms of different EEAs on depressive symptoms.